Developing partnerships: gender, sexuality, and the reformed World Bank - Bedford, Kate (University of Minnesota Press, 2009)
"A nuanced critique of how the World Bank encourages gender norms through its policies, Developing Partnerships argues that financial institutions are key players in the global enforcement of gender and family expectations.By combining analysis of documents produced and sponsored by the World Bank with interviews of World Bank staffers and case studies, Kate Bedford presents a detailed examination of gender and sexuality in the policies of the world's largest and most influential development institution. Looking concurrently at economic and gender policy, Bedford connects reform of markets to reform of masculinities, loan agreements for export promotion to pamphlets for indigenous adolescents advising daily genital bathing, and attempts to strengthen institutions after the Washington Consensus to efforts to promote loving couplehood in response to economic crisis. In doing so, she reveals the shifting relationships between development and sexuality and the ways in which gender policy impacts debates about the future of neoliberalism.Providing a multilayered account of how gender-aware policies are conceived and implemented by the World Bank, Developing Partnerships demonstrates as well how institutional practices shape development."– Site de l'éditeur.
Keywords: LGBTQIA2+; approches et analyses; care; cours; discipline; discours dominant; histoire et politique; hétérosexisme; identités LGBTQIA2+; pol4022; premier cycle; ressource en ligne; science politique; science politique et droit; sciences de la gestion; sexisme; systèmes d'oppressions; thématiques; économie

Un monde vulnérable : pour une politique du care - Tronto, Joan C. (La Découverte, 2009)
« Que signifierait, dans la société contemporaine, prendre au sérieux, comme faisant partie de notre définition d'une société bonne, les valeurs de care - prévenance, responsabilité, attention éducative, compassion, attention aux besoins des autres - traditionnellement associées aux femmes et traditionnellement exclues de toute considération politique? » Telle est la question que pose la théoricienne féministe Joan Tronto dans ce livre majeur, qui a largement contribué à renouveler le champ de la philosophie politique dans le monde anglo-saxon. Le care a été longtemps compris comme une qualité féminine moralement positive. La « moralité des femmes » est même apparue à certains comme une stratégie convaincante pour provoquer le changement politique. Or les femmes sont encore largement exclues du pouvoir. Pour sortir de cette impasse théorique et politique, affirme Joan Tronto, il faut cesser d'associer le care à la « moralité des femmes », comme le fait encore Carol Gilligan dans Une voix différente. Il s'agit plutôt de présenter une défense politique de l'éthique du care défini comme « une activité générique qui comprend tout ce que nous faisons pour maintenir, perpétuer et réparer notre "monde", de sorte que nous puissions y vivre aussi bien que possible ». Tronto considère qu'à condition de déplacer les frontières entre morale et politique, raison et monde des sentiments et entre vie publique et sphère privée, le care peut apparaître comme un concept politique utile, susceptible de nous aider à repenser la coopération démocratique d'êtres qui sont tous fondamentalement vulnérables, comme l'est aussi leur monde."–Page 4 de la couverture.
Keywords: approches et analyses; care; cours; discipline; discours dominant; har4600; histoire et politique; justice sociale; premier cycle; projet charge mentale; rapports sociaux de sexe; science politique; science politique et droit; soin; systèmes d'oppressions; thématiques

The Cyborg Embryo: Our Path to Transbiology - Franklin, S. (THEORY CULTURE AND SOCIETY, 2006)
It is useful on the occasion of the 21st anniversary of the ‘Cyborg Manifesto’ not only to reconsider its lessons in the context of what is frequently described as the re-engineering of ‘life itself’, but to look at Haraway’s earlier work on embryos. In this article I begin with Haraway’s analysis of embryology in the 1970s to suggest her cyborg embryo was already there, and has, if anything, gained relevance in today’s embryo-strewn society. I argue further, as the title suggests, that the cyborg embryo has been crucial in defining our path to what I am calling here, building on Haraway’s notion of trans from Modest_Witness, ‘transbiology’ - broadly meaning stem cell research, cloning, tissue engineering and regenerative medicine. To illustrate this argument I draw on recent ethnographic fieldwork in a new stem cell derivation facility in the UK built adjacent to an IVF surgery. Using this example, I explore the important and paradoxical role of IVF in the emergence of stem cell science, cloning and transbiology, suggesting that Haraway’s analysis remains crucial to understanding the ironic and contradictory, and unexpectedly generative, circumstances through which the IVF-stem cell interface - the door to transbiology - came into being.
Keywords: approches et analyses; biologie; care; corps; cours; discipline; discours dominant; fecondation in vitro; féminisme cyborg; justice reproductive; lit4700; maternité; premier cycle; ressource en ligne; santé; sciences; sciences humaines; sociologie; systèmes d'oppressions; thématiques

La haine et l'amour, la boîte noire du féminisme? Une critique de l'éthique du dévouement - Molinier, Pascale (Nouvelles Questions Feministes, 2004)
Les soins étant réalisés majoritairement par des femmes, on tend à considérer l’amour (des malades, des enfants) « naturel » et normal. Or, le travail de soin peut également générer de la haine envers les personnes dépendantes. Celle-ci n’est pas moins normale que l’amour et sa prise en compte modifie l’analyse des situations de soins. Pour l’heure, la haine est occultée dans les traditions savantes, en particulier dans les théories de l’éthique du dévouement, comme dans les témoignages des travailleuses, ainsi que le suggère une enquête réalisée auprès d’auxiliaires de puériculture. Il en résulte un déficit de visibilité du travail qui permet de conjurer la haine et la violence
Keywords: approches et analyses; care; discipline; discours dominant; projet charge mentale; psychologie; ressource en ligne; sciences humaines; sexisme; soins aux enfants; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; violences